PENGGUNAAN MEDIA CERITA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA NYARING DI SD NEGERI 1 LANDUNGSARI, KABUPATEN MALANG - Wicaksono, Antonius Alam; Anwar, Moh. Farid Nurul; Sepia, Angelina (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
This study aims to improve the ability to read aloud in grade IIA students of SD Negeri 1 Landungsari, Malang Regency, using picture story media. This ability was to devoted to the content of Indonesian with Theme 3, Subtheme 4, namely My Duty in Community Life. This study used two cycles in classroom action research (PTK). In the first cycle, the implementation of learning reached a score of 83.3%, which then increased to 100% in the second cycle. Teacher response was recorded at 85% in the first cycle and increased to 95% in the second cycle. Similarly, student responses reached 82.9% in the first cycle and increased to 90.8% in the second cycle. In cycle I the average percentage value was 61.1% with class completeness of 50%, then in meeting II it had an average percentage value of 68.8% with a class completeness rate of 63.6%. In cycle II, the percentage value increased to 72.7% with a grade completion rate of 77.2%, and meeting II had an average percentage value of 83.6% with a grade completion rate of 86.3%. Which means that the application of picture story media is effective and has a role in the process of reading aloud skills of grade IIA students of SD Negeri 1 Landungsari, Malang Regency.